ANALYSIS OF MARKETING STRATEGIES ON CUSTOMER SATISFACTION AND LOYALTY AT PT. INDOMARCO PRISMATAMA - Nuryadi Nuryadi; Nur Hidayah; Yoga Putra Permana; Muhtar Muhtar; Priyo Utomo (WORLDVIEW ( Development economic and sharia studies journal ), 2022)
This study aims to determine how marketing strategies affect customer satisfaction, how marketing strategies affect customer loyalty. Companies must have effective methods to improve optimal marketing strategies. The method that the researcher uses in this research is the qualitative method, the data analysis method uses descriptive data analysis, which is carried out through interviews in accordance with the provisions. Based on the results of this study, it is stated that the marketing strategy is very influential on customer satisfaction, which is evidenced by the perceived quality of customers when shopping at Indomaret. Forming trust and consumers tend to believe when they already know and know the optimal service at Indomaret in the East Java area. Marketing strategy is also very influential on customer loyalty, this is evidenced by repurchasing (repeat orders) and positive responses that support and agree if the goods sold at Indomaret are safe and reliable so that consumer confidence in the goods or products becomes high and weak so that it can affect interest buy.